The Influence of Kaizen Culture and Compensation on Employee Performance at Grand Medistra Lubuk Pakam Hospital - Tambunan, Zaini Perdana Maksum; Harahap, Kartini (Cattleya Darmaya Fortuna, 2023)
Human resources are one of the organizational resources as an important role in the successful implementation of organizational goals. Grand Medistra Lubuk Pakam Hospitalis a private hospital located in the Deli Serdang and was established on December 9, 2009. Based on preliminary research, it is known that Grand Medistra Hospital supports government programs and has served Universal Health Coverage patients as well as serving general and general patients. The researcher was aware of the conditions at Grand Medis-tra Lubuk Pakam Hospital by looking at the performance of employees, it is known that there were some employees who had high work loyalty and good performance but there were also employees whose performance was mediocre. In addition, employees at Grand Medistra Lubuk Pakam Hospital receive a fairly small compensation.